Desain Kurikulum Pendidikan Agama Kristen untuk Lansia: Pendekatan Kurikulum Deliberasi Jack Swacb - Stefanus Roy Arjuna Manurung; Hasudungan Sidabutar (Harati: Jurnal Pendidikan Kristen, 2024)
Deliberation curriculum is a curriculum design that starts from problems and moves towards solving problems through a deliberation process. This article is an effort made to answer the needs of the elderly in their lives through a coaching or education process by creating a curriculum design specifically for the elderly with the aim of enabling the elderly to share experiences during their productive years among the wider community. The aim of writing the article is to design a Christian Religious Education (PAK) Elderly curriculum based on the deliberation curriculum. The research method used in this article is a descriptive qualitative research method with a literature review approach. The research results found that the deliberation-based curriculum was very effective for elderly PAK because the elderly were not only used as objects but also as subjects. For this reason, when churches and social foundations want to design a curriculum for the elderly, they need to apply a deliberation curriculum approach.